The Economic Viability of Alternative Wetting and Drying Irrigation in Arkansas Rice Production. (1st March 2015) - Nalley, Lanier; Linquist, Bruce; Kovacs, Kent; Anders, Merle
Abstract : As water becomes scarcer in rice ( Oryza sativa L.) production regions throughout the world, producers are becoming aware of the importance of increasing water use efficiency. Thus, new rice production methods which increase water use efficiency (WUE) are beginning to be adopted. This study analyzes one such alternative production method and its economic feasibility in Arkansas. Alternate wetting and drying (AWD) irrigation has the potential to address the concerns of groundwater depletion as well as greenhouse gas emissions (GHG) associated with rice production. Field experiments were conducted in 2012 and 2013 in the Arkansas Delta for three different AWD irrigation regimes and compared to continuous flooded rice. Data collection included CH4 and N2 O emissions, grain yields, and irrigation total water use. Relative to continuous flooding WUE increased by 21 to 56% with the adoption of AWD irrigation and global warming potential (GWP) decreased by 45 to 90%. One common criticism of AWD is the potential for reduced yields and subsequent reductions in producer profits. Our results indicate that some AWD regimes are currently economically competitive even without incentives such as GHG reduction payments or water conservation payments. These results suggest that there is currently an economic rationale for adoption of some AWD regimes and those AWD regimes that are not currently economically competitive may be in the future as groundwater levels recede. A county‐level break‐even analysis indicates an additional depth to ground water of only 5 to 10 m will result in other AWD practices evaluated here becoming profitable.